Keeping Mum' : a qualitative study of women drug users' experience of preserving motherhood in Dublin - Woods, Marguerite (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2008)
According to academic accounts, it is not uncommon for women who use illicit drugs to be culturally portrayed in negative stereotypical terms as ‘unfeminine’, 'unclean' and 'immoral'. Nowhere is this more evident than when a woman is both a drug user and a mother, when the stereotype is expanded to describe a person who invariably gives priority to her drug use rather than to her children. Where many studies purport to present objective clinical data which demonstrate that maternal drug use is incompatible with good parenting, the present study - while taking account of professional views on this topic - privileges the lived motherhood experience of women drug users who struggle to combine parenting with drug use. This study is about women, drug use and motherhood in Dublin.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin